Localized cutaneous hyalohyphomycosis by Fusarium spp. over a postsurgical scar: Response to fluconazole - Chetan D Rajput; Sunil Lilani; Kiran Paradeshi; Vasudha S Deore (Wolters Kluwer Medknow Publications, 2019)
Hyalohyphomycosis are opportunistic fungal infections caused by fungi with colorless septate hyphae. Fusarium is a hyalohyphomycetes which can cause localized or disseminated infections depending on host immunity. Our patient had an infectious lesion over the coronary artery bypass grafting (CABG) scar which was not responding to antibacterial treatment. Further investigations revealed it to be localized cutaneous Fusarium infection. The patient was treated with fluconazole 3 mg/kg/day for 3 weeks and responded very well without any recurrence during the next 3 months follow-up. Thus, this case highlights the effectiveness of fluconazole in uncommon fungal infection.